Prevalence of hypoxaemia in children with pneumonia in low-income and middle-income countries: a systematic review and meta-analysis. Issue 3 (March 2022) - Rahman, Ahmed Ehsanur; Hossain, Aniqa Tasnim; Nair, Harish; Chisti, Mohammod Jobayer; Dockrell, David; Arifeen, Shams El; Campbell, Harry
Summary: Background: Pneumonia accounts for around 15% of all deaths of children younger than 5 years globally. Most happen in resource-constrained settings and are potentially preventable. Hypoxaemia is one of the strongest predictors of these deaths. We present an updated estimate of hypoxaemia prevalence among children with pneumonia in low-income and middle-income countries. Methods: We conducted a systematic review using the following key concepts "children under five years of age" AND "pneumonia" AND "hypoxaemia" AND "low- and middle-income countries" by searching in 11 bibliographic databases and citation indices. We included all articles published between Nov 1, 2008, and Oct 8, 2021, based on observational studies and control arms of randomised and non-randomised controlled trials. We excluded protocol papers, articles reporting hypoxaemia prevalence based on less than 100 pneumonia cases, and articles published before 2008 from the review. Quality appraisal was done with the Joanna Briggs Institute tools. We reported pooled prevalence of hypoxaemia (SpO2 <90%) by classification of clinical severity and by clinical settings by use of the random-effects meta-analysis models. We combined our estimate of the pooled prevalence of pneumonia with a previously published estimate of the number of children admitted to hospital due to pneumonia annually to calculate the total annual number of children admitted to hospital with hypoxaemic pneumonia. Findings: We identified 2825 unique records from the databases, of which 57 studies met the eligibility criteria: 26 from Africa, 23 from Asia, five from South America, and four from multiple continents. The prevalence of hypoxaemia was 31% (95% CI 26–36; 101 775 children) among all children with WHO-classified pneumonia, 41% (33–49; 30 483 children) among those with very severe or severe pneumonia, and 8% (3–16; 2395 children) among those with non-severe pneumonia. The prevalence was much higher in studies conducted in emergency and inpatient settings than in studies conducted in outpatient settings. In 2019, we estimated that over 7 million children (95% CI 5–8 million) were admitted to hospital with hypoxaemic pneumonia. The studies included in this systematic review had high τ 2 (ie, 0·17), indicating a high level of heterogeneity between studies, and a high I 2 value (ie, 99·6%), indicating that the heterogeneity was not due to chance. This study is registered with PROSPERO, CRD42019126207. Interpretation: The high prevalence of hypoxaemia among children with severe pneumonia, particularly among children who have been admitted to hospital, emphasises the importance of overall oxygen security within the health systems of low-income and middle-income countries, particularly in the context of the COVID-19 pandemic. Even among children with non-severe pneumonia that is managed in outpatient and community settings, the high prevalence emphasises the importance of rapid identification of hypoxaemia at the first point of contact and referral for appropriate oxygen therapy. Funding: UK National Institute for Health Research (Global Health Research Unit on Respiratory Health [RESPIRE]; 16/136/109).